2008
DOI: 10.1111/j.1468-1331.2008.02311.x
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term functional status in patients with Guillain‐Barré syndrome

Abstract: Relatively independent from various variables at onset, patients with GBS seem to have a reduced quality of life and functioning, and the distress seems to have become persistent after the first few years with improvement following the acute disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…As previously shown in Guillain Barré syndrome (GBS), our findings suggest, that fatigue is independent from muscle strength, sensory function and the Hughes score (Merkies et al, 1999;Rudolph et al, 2008). Axonal degeneration at long-term follow-up is typical in CIP and may also occur in GBS (Wolfe and Barohn, 1998;Dornonville and Jakobsen, 2005).…”
Section: Discussionsupporting
confidence: 79%
“…As previously shown in Guillain Barré syndrome (GBS), our findings suggest, that fatigue is independent from muscle strength, sensory function and the Hughes score (Merkies et al, 1999;Rudolph et al, 2008). Axonal degeneration at long-term follow-up is typical in CIP and may also occur in GBS (Wolfe and Barohn, 1998;Dornonville and Jakobsen, 2005).…”
Section: Discussionsupporting
confidence: 79%
“…Notably lower scores on physical dimensions have also been found in cross-sectional studies of HRQL several years after GBS, using the SIP [31] and the SF-36 [14,32]. Thus, it seems that persons with GBS recover quite well in terms of the psychosocial aspects of HRQL.…”
Section: Discussionmentioning
confidence: 82%
“…A good outcome after GBS has mostly been associated with the capability to regain walking ability, which is often assessed with the GBS disability score [10,11]. Apart from physical disabilities, studies have shown decreased health-related quality of life (HRQL) and higher fatigue 3-8 years after GBS onset [12][13][14]. Subjective experiences of HRQL and fatigue also seem to differ between persons with residual symptoms and those who have fully recovered [12].…”
Section: Introductionmentioning
confidence: 99%
“…The patients in this study reported severe fatigue as one of the most important symptoms leading to problems in school or work. Fatigue is also an important complaint after GBS in adults, which may in part be attributed to residual peripheral nerve damage (Merkies et al, ; Rudolph et al, ; Rekand et al, ; Drenthen et al, ). Garssen et al ( ) demonstrated a persistent decrease in fatigue after a bicycle exercise training program in adult GBS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although most patients show a tendency to recover and proven effective treatments are available, GBS often has considerable long‐term effects (Bernsen et al, ) . Patients may have persistent neurological deficit, one‐third of patients report persistent pain and up to 60% report severe fatigue interfering with daily life (Merkies et al, ; Rudolph et al, ; Rekand et al, ) . This may have a negative impact on work, quality of life (QoL), and social functioning (Bernsen et al, ; Rudolph et al, ) .…”
Section: Introductionmentioning
confidence: 99%